Respon Pertumbuhan dan Hasil Tanaman Kubis (Brassica oleraceae L.) Varietas Sehati F1 Akibat Pemberian Pupuk Limbah Jamur Tiram - Dicki Mulyana; Muharram Muharram; Darso Sugiono (Peneliti.net, 2021)
This study aims to obtain a response to plant growth and yield of the Sehati F1 variety of cabbage (Brassica oleraceae L.) due to the application of oyster mushroom waste fertilizer. The research was conducted in Cikampek Utara Village, Kota Baru District, Karawang Regency, West Java Province. The time of the experiment was carried out from August 2020 to October 2020. The research method used the experimental method with a single factor randomized block design (RBD). There were 9 treatments and repeated 3 times, so there were 27 experimental plots. The treatments were: A = 0 ton / ha without being given oyster mushroom waste fertilizer, B = 10 tonnes / ha of oyster mushroom waste fertilizer, C = 15 ton / ha Oyster mushroom waste fertilizer, D = 20 tons / ha oyster mushroom waste fertilizer, E = 25 tons / ha oyster mushroom waste fertilizer, F = 30 tons / ha oyster mushroom waste fertilizer, G = 35 tons / ha oyster mushroom waste fertilizer, H = 40 tons / ha of oyster mushroom waste fertilizer, I = 45 tons / ha. Observation data were analyzed using analysis of variance and further tested with DMRT at the 5% level. From the results of this experiment, the application of oyster mushroom waste fertilizer and NPK fertilizer had a significant effect on leaf area with yield (213.91) on the application of oyster mushroom waste fertilizer 15 tonnes / ha and had no significant effect on the growth of leaf number, plant height, stemt. The treatment of oyster mushroom waste fertilizer and NPK fertilizer has not been able to increase the yield of the Sehati F1 variety of cabbage.